Fanconi anemia proteins stabilize replication forks - Chien Wang, Lily (2008)
Fanconi anemia (FA) is a recessive genetic disorder characterized by hypersensitivity to crosslinking agents that has been attributed to defects in DNA repair and/or replication. FANCD2 and the FA core complex bind to chromatin during DNA replication; however, the role of FA proteins during replication is unknown. Using Xenopus cell-free extracts, we show that FANCL depletion results in defective DNA replication restart following treatment with camptothecin, a drug that results in DSBs during DNA replication. This defect is more pronounced following treatment with mitomycin C, presumably because of an additional role of the FA pathway in DNA crosslink repair. Moreover, we show that binding of FA core complex proteins during DNA replication follows origin assembly and origin firing and is dependent on the binding of RPA to ssDNA while FANCD2 additionally requires ATR, consistent with FA proteins acting at replication forks. Together, our data suggest that FA proteins play a role in replication restart at collapsed replication forks.